Chains of art offer connection and care. (1st December 2021) - Speter, Tova
Art Therapist Tova Speter shares a sample from Translations: connected art reflecting empathy (c.a.r.e.), a creative example of how engagement in a collaborative art experience can help people feel connected despite being physically isolated. This community art experience was launched in response to the isolating effects of the COVID-19 global pandemic. Over 100 artists participated in nineteen chains of six linked artistic expressions translating the words of the community through art. The six links in each chain offered a creative way to connect, which offset the 6 feet of physical distance we were advised to keep from each other in order to care for each other. This project highlights how art can hold and communicate intention and feeling across modalities as it offers connection and inspiration to a wide audience.